Skladnja in otroški govor - Kranjc, Simona (Jezik in slovstvo, 1999)
The author reviews the development of syntactic theories from Chomsky in the 1950th to cognitive linguistics of the 1990s. Syntactic theory is applied to a special type of linguistic material, viz. child speech, which displays most of the properties of a language system as realised with relation to particularfunctions in texts.
Keywords: Slovene; slovenščina; otroški govor; skladnja; syntax